A windfall of musicians : Hitler's émigrés and exiles in southern California - Crawford, Dorothy L. (Yale University Press, 2009)
This book is the first to examine the brilliant gathering of composers, conductors, and other musicians who fled Nazi Germany and arrived in the Los Angeles area. Musicologist Dorothy Lamb Crawford looks closely at the lives, creative work, and influence of sixteen performers, fourteen composers, and one opera stage director, who joined this immense migration beginning in the 1930s. Some in this group were famous when they fled Europe, others would gain recognition in the young musical culture of Los Angeles, and still others struggled to establish themselves in an environment often resistant to musical innovation. Emphasizing individual voices, Crawford presents short portraits of Igor Stravinsky, Arnold Schoenberg, and the other musicians while also considering their influence as a group--in the film industry, in music institutions in and around Los Angeles, and as teachers who trained the next generation. The book reveals a uniquely vibrant era when Southern California became a hub of unprecedented musical talent.